Market concentration, firm size and innovative activity: A firm-level economic analysis of selected Indian industries under economic liberalization - Kandamuthan Subodh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The economic liberalization in India was expected to boost the economy, particularly the industrial sector through faster technological development. The Schumpeterian hypothesis, which studies the relationship between market structure variables such as firm size and market concentration and their relationship with innovative activity, has been exhaustively tested in the context of the developed countries and India. An attempt is made in the paper to study this relationship with reference to India's economic liberalization. Hoping to overcome some of the problems of the earlier studies conducted in India, the paper tries to develop a new analytical framework for studying this relationship. Innovative activity is conceptualized here as a combination of in-house R&D and the import of technology after India's liberalization. Using probit and tobit models, the study analyses the firm-specific, product-specific and industry-specific factors which affect the investment decision to undertake innovation and the intensity of the innovative activity. The examination is carried out for two industries from the manufacturing sector, viz. drugs and pharmaceuticals and electronics. The probit and tobit estimates indicate that the factors affecting the decision to invest in innovative activity and its intensity differ for the manufacturing industries under review, highlighting the presence of technological opportunities across industries. The analysis also shows that there is no evidence to support the assumption that large-sized firms with market power are more innovative. There are also inter-industry differences in the factors affecting innovative activity, which confirms the role of technological opportunity after economic liberalization in India.
Keywords: L1; L25; O3; 330; market structure; firm size; technological change; Marktstruktur; Industrieökonomik; Betriebsgröße; Technischer Fortschritt; Innovationsmanagement; Indien